Neuropilin‐2 is an independent prognostic factor for shorter cancer‐specific survival in patients with acinar adenocarcinoma of the prostate. Issue 9 (16th October 2019) - Borkowetz, Angelika; Froehner, Michael; Rauner, Martina; Conrad, Stefanie; Erdmann, Kati; Mayr, Thomas; Datta, Kaustubh; Hofbauer, Lorenz C.; Baretton, Gustavo B.; Wirth, Manfred; Fuessel, Susanne; Toma, Marietta; et al.
Abstract : Neuropilin‐2 (NRP2) is a member of the neuropilin receptor family and known to regulate autophagy and mTORC2 signaling in prostate cancer (PCa). Our study investigated the association of immunohistochemical NRP2 expression with clinicopathological data in PCa patients. For this purpose, we generated a tissue microarray with prostate tissue specimens from 400 PCa patients treated by radical prostatectomy. We focused on patients with high‐risk factors such as extraprostatic extension (pT ≥ 3), Gleason score ≥8 and/or the presence of regional lymph node metastases (pN1). Protein levels of NRP2, the vascular endothelial growth factor C (VEGFC) and oncogenic v‐ets avian erythroblastosis virus E26 oncogene homolog (ERG) gene as an indicator for TMPRSS2‐ERG fusion was assessed in relation to the patients' outcome. NRP2 emerged as an independent prognostic factor for cancer‐specific survival (CSS) (hazard ratio 2.360, 95% confidence interval = 1.2–4.8; p = 0.016). Moreover, the association between NRP2 expression and shorter CSS was also especially pronounced in patients at high risk for progression (log‐rank test: p = 0.010). We evaluated the association between NRP2 and the TMPRSS2‐ERG gene fusion status assessed by immunohistochemical nuclear ERG staining. However, ERG staining alone did not show any prognostic significance. NRP2 immunostaining is significantly associated with shorter CSS in ERG‐negative tumors (log‐rank test: p = 0.012). No prognostic impact of NRP2 expression on CSS was observed in ERG‐positive tumors (log‐rank test: p = 0.153). Our study identifies NRP2 as an important prognostic marker for a worse clinical outcome especially in patients with a high‐risk PCa and in patients with ERG‐negative PCa. Abstract : What's new? To date, prognostic biomarkers for prostate cancer (PCa) patients with aggressive disease are still lacking. Neuropilin‐2 (NRP2) has previously been involved in intracellular trafficking, anti‐apoptotic signaling, and autophagy, indicating a potential role in PCa progression. This large cohort study demonstrates an association between NRP2 protein levels in PCa tissues and cancer‐specific survival in patients with localized PCa treated by radical prostatectomy. NRP2 is associated with a worse outcome, especially in high‐risk PCa patients and patients with negative ERG status. NRP2 thus emerges as an independent prognostic biomarker for aggressive PCa and might become a potential target for future therapy strategies.